First results of the observatory in Basilicata: Trend of sheep and goat milk, cheese and meat prices and hygienic-sanitary situation of the farms (PRD 54-97) - Amato A.; Di Gennaro P.; Amato D. (Production systems and product quality in sheep and goats, 2001)
In Basilicata, a survey has been carried out on the trend of the prices of sheep and goat products and on the situation of the farms with regards to the hygienic and sanitary rules. The enquiry showed that meat price decreased during the last three years as well as wool price, whereas cheese price has increased slightly. Farm milk processing takes place mainly in the inlands of the mountains. In the hills, milk is sold to cheese dairies principally out of the region. None of the farms examined was in possession of the sanitary authorization pursuant to the PRD 54-97 (application of the directive EU 92-46).
Meeting of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 1999/09/23-25, Molina de Segura-Murcia (Spain)